Chaste value : economic crisis, female chastity and the production of difference on Shakespeare's stage - Gillen, Katherine (Edinburgh critical studies in Shakespeare and philosophy., 2017)
Chaste Value reassesses chastity's significance in early modern drama, arguing that presentations of chastity inform the stage's production of early capitalist subjectivity and social difference.